Will Robotics Affect the Future of Work? - O. B. Pichkov; A. A. Ulanov (Vestnik MGIMO-Universiteta)
Book review: Matthews, P., S. Greenspan (2020) Automation and Collaborative Robotics: A Guide to the Future of Work. Berkeley, CA, Apress. 285 p.